(untitled) (Contemporary Education and Teaching Research, 2024)
Based on the era background of the ideological and political education of Audit, this paper analyzes the present situation of the reform of the objective, content and mode of the ideological and political education of Audit, based on the 5E model, the paper designs the teaching links, probes into the concrete realization path of the audit teaching course in the application-oriented university, and takes attracting students’ interest as the cut-in point and promoting students’ professional accomplishment as the means, Based on the era background of the ideological and political education of Audit, this paper analyzes the present situation of the reform of the objective, content and mode of the ideological and political education of Audit, based on the 5E model, the paper designs the teaching links, probes into the concrete realization path of the audit teaching course in the application-oriented university. The teaching practice of auditing course is to attract students’ interest in learning, to promote students’ professional quality as a means, and to cultivate students’ professional and cultural self-confidence as a value goal, it provides reference for the teaching practice of Audit Course, and also provides suggestions for strengthening the training of audit talents.